The emerging role of sacubitril/valsartan in pulmonary hypertension with heart failure - Xu, Yu; Yang, Bowen; Hui, Jingjiao; Zhang, Cai; Bian, Xiaoyun; Tao, Min; Lu, Yipeng; Wang, Wei; Qian, Hui; Shang, Zhenglu (Frontiers in Cardiovascular Medicine, 2023)
Pulmonary hypertension due to left heart disease (PH-LHD) represents approximately 65-80% of all patients with PH. The progression, prognosis, and mortality of individuals with left heart failure (LHF) are significantly influenced by PH and right ventricular (RV) dysfunction. Consequently, cardiologists should devote ample attention to the interplay between HF and PH. Patients with PH and HF may not receive optimal benefits from the therapeutic effects of prostaglandins, endothelin receptor antagonists, or phosphodiesterase inhibitors, which are specific drugs for pulmonary arterial hypertension (PAH). Sacubitril/valsartan, the angiotensin receptor II blocker-neprilysin inhibitor (ARNI), was recommended as the first-line therapy for patients with heart failure with reduced ejection fraction (HFrEF) by the 2021 European Society of Cardiology Guidelines. Although ARNI is effective in treating left ventricular (LV) enlargement and lower ejection fraction, its efficacy in treating individuals with PH and HF remains underexplored. Considering its vasodilatory effect at the pre-capillary level and a natriuretic drainage role at the post-capillary level, ARNI is believed to have a broad range of potential applications in treating PH-LHD. This review discusses the fundamental pathophysiological connections between PH and HF, emphasizing the latest research and potential benefits of ARNI in PH with various types of LHF and RV dysfunction.